Mixed Reality Interactive Visualisation for Human Space Missions - Dias, J.; Bastos, R.; Pedro, S. (Proc 7th International Workshop on Simulation for European Space Programmes, ESTEC, Noordwijk, The Netherlands, 2002)
XXX